Endoscopic severity and classification of lesions with pan-enteric capsule endoscopy and ileocolonoscopy in ileocolonic Crohn’s disease - Brodersen, Jacob Broder; Kjeldsen, Jens; Knudsen, Torben; Jensen, Michael Dam (Endoscopy International Open, 2023)
Background and study aims Recent evidence supports the use of pan-enteric capsule endoscopy (CE) for the diagnosis and follow-up of Crohn’s disease (CD). The aim of this study was to examine the agreement between CE and ileocolonoscopy (IC) for determining the severity and classification of lesions in ileocolonic CD.Patients and methods In a prospective blinded multicenter study, patients with suspected CD were examined with CE and IC within 2 weeks. Ninety-nine participants with a full IC and CE were included in the analysis. The ileocolonic disease severity was assessed with the Simple Endoscopic Score for Crohn’s Disease (SES-CD).Results CD was diagnosed in 30 patients with IC and CE. The mean SES-CD was 9.8 (CI 7.9–11.8) and 10.6 (CI 8.2–13.1), respectively (P = 0.69). There was a substantial agreement (ICC 0.83, CI 0.68–0.92) and a strong correlation between SES-CD assessed with IC and CE (rs = 0.78, P < 0.001). 55 bowel segments had ulcerations with both modalities (terminal ileum 24, right colon 12, transverse colon eight, left colon eight and rectum three). Mean sub-scores for ulcer size, area of ulcerated surface and area of affected surface did not differ between modalities. The inter-modality agreement (κ) was 0.46, 0.34 and 0.43, respectively (P < 0.001). Conclusions There is a strong correlation between IC and CE for the severity of ileocolonic CD. The agreement for SES-CD sub-scores is fair to moderate. CE could be an alternative to IC for the assessment of endoscopic severity in selected patients with suspected CD.